Dorsal teratoma simulating an upper limb associated with a diastematomyelia - Ahmed Kane; Ahmed Salem Kleib; Cheikh Diouf; Sidi Mohamed Nagi; Elhadj Ada; Yacoub Mohamed Sghair; Sidi Wafi Baba (Elsevier, 2021)
Introduction: The association of a diastematomyelia with a dorsal teratoma simulating an accessory limb is a very rare condition, the management of which being controversial. Observation: A female newborn presented to us for the management of a dorsal midline mass simulating an upper extremity. The rest of the clinical exam and particularly the neurologic exam were normal. A complete CT scan and a thoracic and lumbar MRI confirmed a diastematomyelia type I and a structure appearing as an incomplete upper extremity possessing a scapula, a humerus, and two digits arising from a widening between the vertebral column. The surgical resections of this apparent accessory limb were accomplished without complications. The pathologic examination showed a mature teratoma with gastro-intestinal, cutaneous, and cartilaginous tissues. Conclusion: A newborn presenting with a dorsal mass simulating an accessory limb must have a CT-scan and an MRI to detect associated split cord malformation (SCM).